Intravenous fosphenytoin therapy for rescue of acute trigeminal neuralgia crisis in patients awaiting neurosurgical procedures: A cross-sectional study. (December 2021) - Noro, Shusaku; Seo, Yoshinobu; Honjo, Kaori; Okuma, Masahiro; Asayama, Bunsho; Amano, Yuki; Kyono, Masanori; Sako, Kazuya; Nakamura, Hirohiko
Highlights: Few treatments exist for acute attacks of trigeminal neuralgia. Patients who received intravenous fosphenytoin therapy were reviewed retrospectively. Reduction in pain 24 h following treatment was significant with no adverse effects. Intravenous fosphenytoin may be used to treat acute trigeminal neuralgia crisis. Abstract: Few treatments exist for acute attacks of trigeminal neuralgia. Therefore, this study aimed to investigate the efficacy and safety of an intravenous fosphenytoin therapy protocol in a trigeminal neuralgia crisis. We conducted a single-center, retrospective, observational study of the records of 20 patients with trigeminal neuralgia who received intravenous fosphenytoin therapy (15 mg/mL in normal saline at 50 mg/min for 15 min, total 750 mg) during hospitalization between September 2015 and August 2020. Serum phenytoin concentration was measured 30 min post-infusion. Pain severity was evaluated using a numerical rating scale and was analyzed for statistical significance. The mean age of the patients was 67.5 years (female, 50.0%). The median numerical rating scale score (interquartile range) of pain severity was 2.35 (0–10), 0.65 (0–5), 0.15 (0–1), 2.00 (0–8), and 4.30 (0–10) at 15, 30, and 60 min, and 12 and 24 h, respectively ( p  < .001); the numerical rating scale score was 10 before treatment. Reduction in pain 24 h following treatment was significant. The mean phenytoin concentration was 12.8 μg/mL 30 min post-treatment. While mild dizziness occurred in four patients, all could walk independently within 60 min. The mean age and weight of patients with mild dizziness were significantly higher and lower, respectively ( p  < .001), than those of other patients. These results may provide physicians with new insights into the innovative therapeutic option of intravenous fosphenytoin and contribute to advancements in treating acute trigeminal neuralgia crisis.